Growth Promoting Rhizospheric and Endophytic Bacteria from Curcuma longa L. as Biocontrol Agents against Rhizome Rot and Leaf Blight Diseases - Vinayarani, G. (Plant Pathol J, 2018)
Plant growth promoting rhizobacteria and endophytic bacteria were isolated from different varieties of turmeric (Curcuma longa L.) from South India. Totally 50 strains representing, 30 PGPR and 20 endophytic bacteria were identified based on biochemical assays and 16S rDNA sequence analysis. The isolates were screened for antagonistic activity against Pythium aphanidermatum (Edson) Fitzp., and Rhizoctonia solani Kuhn., causing rhizome rot and leaf blight diseases in turmeric, by dual culture and liquid culture assays. Results revealed that only five isolates of PGPR and four endophytic bacteria showed more than 70% suppression of test pathogens in both assays. The SEM studies of interaction zone showed significant ultrastructural changes of the hyphae like shriveling, breakage and desication of the pathogens by PGPR B. cereus (RBac-DOB-S24) and endophyte P. aeruginosa (BacDOB-E19). Selected isolates showed multiple Plant growth promoting traits. The rhizome bacterization followed by soil application of B. cereus (RBacDOB-S24) showed lowest Percent Disease Incidence (PDI) of rhizome rot and leaf blight, 16.4% and 15.5% respectively. Similarly, P. aeruginosa (BacDOB-E19) recorded PDI of rhizome rot (17.5%) and leaf blight (17.7%). The treatment of these promising isolates exhibited significant increase in plant height and fresh rhizome yield/plant in comparison with untreated control under greenhouse condition. Thereby, these isolates can be exploited as a potential biocontrol agent for suppressing rhizome rot and leaf blight diseases in turmeric.